Infrastructure Barriers to Islamic Political Parties: Dynamics of PKB in the 2004-2019 Presidential Election Contestation - M Nastain; Abdullah, Irwan; Qodir, Zuly; Jubba, Hasse (International Journal of Social Science and Religion (IJSSR), 2024)
This research was intended to determine the infrastructural barriers of the PKB political party in encouraging its cadres to become contestants in the presidential and vice-presidential elections from 2004 to 2019. During the four presidential and vice-presidential elections, PKB, one of Indonesia's largest Islamic parties, was absent from sending its cadres as contestants. This failure is suspected to result from infrastructural obstacles that intersect with PBNU's political interests. This research used a qualitative approach by combining interviews with documentation data and direct observations in the field. Interview data findings were used as a guide for finding online or offline documentation data. Both findings confirmed each other and were combined with observational data as a data validation method. Data presentation was carried out in three main stages. Namely, data findings were reduced according to research needs and elaborated using Anthony Giddens' structuration thinking. The data findings in this research reveal that there are infrastructural obstacles in the form of organizational patrons that disrupt the independence of PKB. There is also extra organizational power from the NU autonomous division, which is suspected to have sectoral interests. Apart from that, external intervention makes PKB's political steps less flexible.